Identification and characterization of a novel canine circovirus with truncated replicate protein in Sichuan, China - Cao, Liang; Li, Suyao; Xin, Jialiang; Liao, Yanjun; Li, Chenghui; Peng, Guangneng (Frontiers in Veterinary Science, 2024)
Canine circovirus (CanineCV) is a recently identified member of the Circoviridae family. Since its discovery in 2011, CanineCV has been detected in different countries worldwide, infecting both domestic and wild canids. The virus is potentially associated with gastrointestinal and respiratory illnesses. In 2016, CanineCV was reported in the southwestern region of Guangxi, China. However, its prevalence in other provinces in the Southwest region remained unknown. This study collected a total of 208 serum samples from domestic dogs in Sichuan, China in 2022 to investigate the prevalence of CanineCV. Among these samples, 26 tested positive for CanineCV, resulting in a positivity rate of 12.5%. Additionally, 12 strains were sequenced, 9 of which had a sequence length of 2,063 nucleotides (nt), 2 of the other threes had a length of 2,062 nts and another was 2,064 nt. Notably, a frameshift mutation was identified, resulting in a truncated ORF1 and the occurrence of a novel sequence comprised of 13 amino acids at the end of the Rep protein. This mutation could affect the replication cycle of the virus. Phylogenetic and evolutionary analyses revealed that the isolates belonged to the CanineCV-3 genotype and were prevalent in the Southeast and the Southwest regions of China, as well as in the neighboring countries alongside other strains of the same genotype. Collectively, this epidemiological investigation widens our understanding of the genetic diversity of CanineCV in Southwest China and provides insights into viral evolution.